واقع ممارسة الانشطة البدنية والرياضية للجمعيات الرياضية في ولاية سوق أهراس - بخوش اسامة (My University, 2024)
: الملخص عنـوان الدراسـة: الأنشطة البدنية والرياضية للرياضات الفردية في الجمعيات الرياضية لولاية سوق اهراس • هـدف الدراسـة:  تحديد اهم العراقيل التي تعيق ممارسة الأنشطة البدنية والرياضية في الرياضات الفردية.  التعرف على واقع تكوين المدربين في الرياضات الفردية.  تبيين دور الاولياء والمسؤولين نحو تشجيع الناس على ممارسة الأنشطة البدنية والرياضية للرياضات الفردية. • فرضـيات الدراسـة:  هناك عراقيل تعيق ممارسة الأنشطة البدنية والرياضية في الرياضات الفردية  واقع ضعيف الاداء لتكوين المدربين في الرياضات الفردية.  هناك نسبة منخفضة من الاولياء والمسؤولين لتشجيع الناس على ممارسة الأنشطة البدنية والرياضية للرياضات. • إجـراءات الدراسـة الميدانيـة: العينـة: تم أخذ العينة من 90 فرد أي بنسبة 55.90 % من المجتمع الكلي حيث تم اختيارهم بطريقة قصديةمن رؤساء الجمعيات الرياضية لولاية - سوق أهراس- المجـال الـزماني: من المعروف منهجيا أن يحدد الباحث الفترة الزمنية التي نزل فيها إلى الميدان وفي الدراسة الحالية قامت مجموعة البحث بدراسة إستطلاعية على رؤساء الجمعيات الرياضية - سوق أهراس، وقد إقتصر هذا على الفترة الممتدة من 15 اكتوبر 2023 إلى غاية 25 افريل 2024. المجال المكاني: تمت الدراسة على مستوى الجمعيات الرياضية - سوق أهراس- • المنهـج المستخـــدم: تم إستخدام المنهج الوصفي المسحي. • الأدوات المستعملـــة: إعتمدنا في دراستنا على إستمارة استبيان. • النتائج المتـوصل إلـيها: لقد تم التوصل إلى النتائج التالية:  للعوامل البيئة المحيطة، مثل الطقس السيء أو نقص البنية التحتية الرياضية، أن تعيق ممارسة الرياضات الفردية.  الإصابات الشائعة تعد عائقًا رئيسيًا لممارسة الرياضات الفردية.  لقلة الوقت المتاح والجداول الزمنية المزدحمة تعيق الأفراد من ممارسة الرياضات الفردية.  للمشكلات المالية، مثل تكاليف المعدات الرياضية أو الرسوم للانضمام إلى الأندية، تعيق ممارسة الرياضات الفردية. إستخـلاصات واقتراحــات:  دراسة التحديات التي تواجه تطوير وتعزيز الرياضات الفردية داخل الجمعيات الرياضية.  تقييم مستوى الإقبال والمشاركة في الأنشطة البدنية والرياضية للرياضات الفردية بين أفراد المجتمع.  تحليل دور الجمعيات الرياضية في تعزيز الوعي وتشجيع الشباب على ممارسة الرياضات الفردية ودورها في بناء الشخصية وتعزيز الانضباط الذاتي.  تقديم مقترحات لتحسين وتطوير برامج الأنشطة البدنية والرياضية للرياضات الفردية داخل الجمعيات الرياضية. ABSTRACT : • Study Objective:  Identify the most important obstacles that hinder the practice of physical activities and sports in individual sports.  Learn about the reality of training trainers in individual sports.  Demonstrate the role of parents and officials towards encouraging people to engage in physical activities and sports for individual sports. • Hypotheses of the study:  There are obstacles to physical and sports activities in individual sports  A poorly performing reality for the training of trainers in individual sports.  There is a low percentage of guardians and officials to encourage people to engage in physical activities and sports for sports. • Field Study Procedures: Sample: The sample was taken from 90 individuals, or 55.90% of the total community, as they were intentionally selected from the headsof sports associations of the Wilayat of Souk Ahras. Time domain: It is known systematically that the researcher determines the period of time in which he went to the field. In the current study, the research group conducted a prospective study on the heads of sports associations - Souk Ahras. This was limited to the period from October 15, 2023 to April 25, 2024. Spatial field: The study was conducted at the level of sports associations - Souk Ahras - • The method used: The descriptive survey method was used. • Tools used: In our study, we relied on a questionnaire form. • Findings: The following findings have been made:  Surrounding environmental factors, such as bad weather or lack of sports infrastructure, can hinder individual sports.  Common injuries are a major barrier to individual sports.  Lack of available time and busy schedules hinder individuals from practicing individual sports.  Financial problems, such as the costs of sports equipment or fees to join clubs, hinder the practice of individual sports. Conclusions and Suggestions:  Studying the challenges facing the development and promotion of individual sports within sports associations.  Evaluate the level of turnout and participation in physical and sports activities for individual sports among members of the community.  Analyze the role of sports associations in promoting awareness and encouraging young people to practice individual sports and their role in building personality and promoting self-discipline.  Submit proposals to improve and develop programs of physical and sports activities for individual sports within sports associations. résumé : Objectif de l'étude: • Déterminer les principaux obstacles à la pratique des activités physiques et sportives dans les sports individuels. • Découvrir la réalité de la formation des entraîneurs dans les sports individuels. • Mettre en évidence le rôle des parents et des responsables dans l'encouragement des gens à pratiquer des activités physiques et sportives dans les sports individuels. Hypothèses de l'étude: • Il existe des obstacles qui entravent la pratique des activités physiques et sportives dans les sports individuels. • La réalité de la formation des entraîneurs dans les sports individuels est faible en performance. • Il y a un faible pourcentage de parents et de responsables qui encouragent les gens à pratiquer des activités physiques et sportives. Procédures de l'étude sur le terrain: • Échantillon: L'échantillon a été composé de 90 personnes, soit 55,90 % de la population totale, choisies de manière intentionnelle parmi les présidents des associations sportives de la wilaya de Souk Ahras. • Période de l'étude: Conformément à la méthodologie, la période de descente sur le terrain a été définie du 15 octobre 2023 au 25 avril 2024 pour cette étude exploratoire menée auprès des présidents des associations sportives de Souk Ahras. • Lieu de l'étude: L'étude a été réalisée au sein des associations sportives de la wilaya de Souk Ahras. Méthodologie utilisée: • Méthode descriptive par enquête. Outils utilisés: • Questionnaire. Résultats obtenus: • Les facteurs environnementaux, comme les mauvaises conditions météorologiques ou le manque d'infrastructures sportives, peuvent entraver la pratique des sports individuels. • Les blessures courantes sont un obstacle majeur à la pratique des sports individuels. • Le manque de temps et les emplois du temps chargés empêchent les individus de pratiquer des sports individuels. • Les problèmes financiers, tels que le coût de l'équipement sportif ou les frais d'adhésion aux clubs, entravent la pratique des sports individuels. Conclusions et propositions: • Étudier les défis qui entravent le développement et la promotion des sports individuels au sein des associations sportives. • Évaluer le niveau de participation et d'engagement dans les activités physiques et sportives des sports individuels parmi la population. • Analyser le rôle des associations sportives dans la sensibilisation et l'encouragement des jeunes à pratiquer des sports individuels, ainsi que leur rôle dans le développement personnel et la discipline. • Proposer des améliorations et des développements pour les programmes d'activités physiques et sportives des sports individuels au sein des associations sportives.
Keywords: • الأنشطة البدنية و الرياضية; • الرياضات الفردية; • الجمعيات الرياضية; • Physical and sports activities; • Individual sports; • Sports clubs; • Activités physiques et sportives; • Sports individuels; • Associations sportives